ANALISIS PRODUKSI PERIKANAN LAUT, BUDIDAYA LAUT, TAMBAK, DAN KOLAM, PERIKANAN TANGKAP DI KABUPATEN REMBANG - Soebandriyo Soebandriyo (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
Nature of qualitative descriptive study, research sites Rembang the research objectives: 1.For improve the condition of marine fisheries in the district of Apex, 2.Untuk improve conditions for fish farm in the district of Apex, 3.For improve the condition of marine aquaculture, ponds and pools in the District of Apex. Informant: Department of Fisheries and Maritime Affairs, Planning, Field Extension, Fishing, Officer TPI, Officer KUD, and processing fish. The results In accordance with the geographical area, the District Apex has the potential fishery (both land and sea) with huge potential. Particular sector of marine fisheries, Rembang Menem starch ranked third sewilayah Central Java, after Pekalongan and Pati. Looking at things that way, then the sea fishery sector to be one among the mainstay for regional economic development. In this effort the government Rembang plan to gradually realize the development in the field of marine and fisheries with a special program for the Planning Area Maritime Integrated. Various policies issued government in the fisheries sector is not always profitable for fishermen. The absence of infrastructure that is easy to access fishing/companies fisheries, in addition to increased knowl knowledge/skills they are in the process of the catch, Policy Ministry of Fisheries and Maritime (CTF) to provide intensive for venture provides an opportunity fishery has not touched the tiny fishing, especially for workers fishermen, for the assistance of the government in the form of capital or equipment such as boat engines, fishing gear, boats, and a net gain instead of the fishing skipper who has the condition of the economy is very advanced, fishing workers get no help from the government